2012
DOI: 10.3109/14767058.2011.648233
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL-4, IL-8, IL-12, interferon-γ and CRP levels in pregnant women with preeclampsia, and their relation with severity of disease and fetal birth weight

Abstract: Elevated maternal serum pro-inflammatory cytokine IL-8 and CRP in severe preeclamptic women compared with normal pregnant women supports the hypothesis that preeclampsia is associated with increased inflammatory responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 50 publications
3
34
1
Order By: Relevance
“…Our findings do not reflect the pro-inflammatory environment in PE shown in other studies [2426], however differences in study designs exist in relation to sample population, pregnancy status, and sampling techniques.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings do not reflect the pro-inflammatory environment in PE shown in other studies [2426], however differences in study designs exist in relation to sample population, pregnancy status, and sampling techniques.…”
Section: Discussioncontrasting
confidence: 99%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been repeatedly shown that CRP levels are elevated in pregnancies that become complicated by preeclampsia (14, 32, 33). In this study, women who are genetically predisposed to higher levels of CRP are protected against preeclampsia.…”
Section: Discussionmentioning
confidence: 99%